Mappings and decompositions of pairwise continuity on pairwise nearly Lindelof spaces. - Kilicman, Adem; Salleh, Zabidin (AulonaPress, 2010)
The purpose of this paper is to study the effect of mappings, some decompositions of pairwise continuity and some generalized pairwise open mappings on pairwise nearly Lindelof spaces. The main result indicates that a pairwise -continuous image of a pairwise nearly Lindelof space is pairwise nearly Lindelof.